Experimental Study of the Effects of Collision of Water Droplets in a Flow of High-Temperature Gases - Antonov D. V. Dmitry Vladimirovich; Volkov R. S. Roman Sergeevich; Kuznetsov G. V. Geny Vladimirovich; Strizhak P. A. Pavel Alexandrovich (2016, 2016)
Title screen